A study on torrefaction of food waste. (15th January 2015) - Poudel, Jeeban; Ohm, Tae-In; Oh, Sea Cheon
Highlights: Food waste undergoing torrefaction was investigated. Gaseous composition of the product gas from torrefaction was studied. The torrefaction range for the food waste was defined considering product gas analysis, the energy yield, and the HHV. Food waste showed energy yield values above 80% for torrefaction range, i.e. between 290 and 330 °C. Abstract: Torrefaction of biomass under anoxic condition can produce an energy dense and consistent quality solid biomass fuel for combustion and co-firing applications. This paper investigates the fuel characteristics of food waste at torrefaction temperatures ranging from 150 to 600 °C, for torrefaction residence time varying from 0 to 50 min in a horizontal tubular reactor. The torrefied products were characterized in terms of their elemental composition, energy yield, ash content and volatile fraction. The gaseous products from torrefaction of food waste were also analyzed. Thermogravimetric analysis was carried out in order to obtain the kinetic parameters for the torrefaction reaction of food waste. It was found that the food waste undergoes changes in their physical and chemical properties during torrefaction. The energy and mass yield were also found to decrease with an increase in the torrefaction temperature, whereas the higher heating value increased.